If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + -7) = 9x + 5 Reorder the terms: 4(-7 + 3x) = 9x + 5 (-7 * 4 + 3x * 4) = 9x + 5 (-28 + 12x) = 9x + 5 Reorder the terms: -28 + 12x = 5 + 9x Solving -28 + 12x = 5 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -28 + 12x + -9x = 5 + 9x + -9x Combine like terms: 12x + -9x = 3x -28 + 3x = 5 + 9x + -9x Combine like terms: 9x + -9x = 0 -28 + 3x = 5 + 0 -28 + 3x = 5 Add '28' to each side of the equation. -28 + 28 + 3x = 5 + 28 Combine like terms: -28 + 28 = 0 0 + 3x = 5 + 28 3x = 5 + 28 Combine like terms: 5 + 28 = 33 3x = 33 Divide each side by '3'. x = 11 Simplifying x = 11
| 2+3(x+2)=2 | | 4(-2x+6)=72 | | 3(37)-x=74 | | 8x-141=19 | | 3(5x+8)=144 | | 9-16= | | 4(1x-8)=0 | | 5(4x+2)=-30 | | 2(6x-8)=68 | | 7(x+2)=5x+21 | | 5(6x+8)=-320 | | 8(x+2)-9= | | 3x+6=-82-5x | | -x+6=21-4x | | 8-x+5x-2-9x= | | 3x+4=-10+5x | | 3-7x=-5x-21 | | -2+5x+5x=68 | | 5x-3=5x+3 | | 4.3-1.4*(p+7)=-9.7 | | 7x-8+6x=-8 | | x+3+2x=39 | | 9+7x=58 | | 3*-1.33333333333+4/7= | | -1.33333333333+4/7= | | p(x)=x^2-256 | | -7[3+7(-4+7)]+15= | | 3r+4= | | 3r+4/7=1 | | -2+3x=10 | | 7x+1=-48 | | 5(-4)-(-17)= |